The content clause in spanish. A funtional-typological approach - Alvarado, Carola; Koza, Walter (Lenguas Modernas, 2019)
The objective of this Works is to describe the content clause in Spanish according to the functional-typological approach (Givón, 1990; 2009; Cristofaro, 2003). From this perspective, we raise that morphosyntactic traits of content clauses are determined by the semantic of the verb in the main clause, for this reason, the articulation of those levels allows to analyze the semantic-syntactic integration and to establish a continuum of clause combination (Givón, 2006). For such purpose, we propose an analysis table that considers the following syntactic possibilities: negation, subordinated verb in a non-finite form, subordinated verb in a finite form, subordinated clause in passive form, replacement of the subordinated clause by a clitic; divergence of participants; interference in time, aspect and mode, presence or absence of subordinate, and nominalization.